2018
DOI: 10.1002/ijc.31274
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of SLC1A5 sensitizes colorectal cancer to cetuximab

Abstract: Cetuximab resistance is a key barrier in treating metastatic colorectal cancer (mCRC). Targeting of metabolic resources import could resensitize drug-resistant cancer cells to anticancer treatments. Here we showed that the expression of the glutamine transporter solute carrier 1 family member 5 (SLC1A5) in clinical CRC samples of patients resisted to cetuximab was significantly higher than in those of patients responded to cetuximab. Inhibition of SLC1A5 by shRNA-mediated gene silencing or pharmacological inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…However, its clinical use is limited due to acquired drug resistance. A few previous studies have shown that activation of the EGFR-dependent pathways is regarded as the main cause of drug resistance 9,34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its clinical use is limited due to acquired drug resistance. A few previous studies have shown that activation of the EGFR-dependent pathways is regarded as the main cause of drug resistance 9,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of clinical importance to identify potential novel pathway(s) that mediate this acquired resistance phenotype to achieve better responses to cetuximab. In fact, recent studies have shown that the expression status of a glutamine transporter, solute carrier 1 family member 5 (SLC1A5), in human colorectal cancer patients dictates their response to cetuximab regardless of EGFR/KRAS mutational status, thus highlighting the importance of currently unknown/unrecognized novel molecular pathways driving cetuximab resistance 8,9 . Moreover, inhibiting SLC1A5 significantly enhanced the inhibitory efficacy of cetuximab, suggesting that unknown molecular mechanism(s) may be involved in other human malignancies such as cetuximab-resistant SCC of the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, V-9302 may represent a superior treatment strategy for CRC. A recent paper reports treatment of CRC by combining EGFR-inhibition by cetuximab with inhibition of SLC1A5 through either shRNA knockdown or pharmacological inhibition by l -γ-glutamyl- p -nitroanilide (GPNA) [ 52 ]. The authors observed enhanced efficacy and sensitization of resistant tumors with the combination in vitro and in vivo [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper reports treatment of CRC by combining EGFR-inhibition by cetuximab with inhibition of SLC1A5 through either shRNA knockdown or pharmacological inhibition by l -γ-glutamyl- p -nitroanilide (GPNA) [ 52 ]. The authors observed enhanced efficacy and sensitization of resistant tumors with the combination in vitro and in vivo [ 52 ]. Building upon these promising results and in view of the 100-fold improvement in potency of V-9302 over GPNA [ 51 ], combination therapy with V-9302 and EGFR-targeted antibodies may result in even further improved efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting, immunoprecipitation, and immunofluorescence assays were performed as described previously using specific antibodies listed in Supplementary Table S2 [ 39 , 40 ]. Quantitative real-time PCR was performed using the SYBR Green I Master kit (Roche, Basel, Switzerland) with a LightCycler 480 system as described previously [ 39 , 41 ].…”
Section: Methodsmentioning
confidence: 99%